Organizational factors influencing the adoption of blockchain technology by Deposit-Taking Savings and Credit Cooperative Societies (SACCOs) in Kenya - Kimani, S. W. (Strathmore University, 2025)
DT-SACCOs in Kenya are critical drivers of financial inclusion, serving over 6.4 million members. Despite their significant role, these institutions face fraud, inefficiencies, and governance failures, which hinder their sustainability. Blockchain technology offers transformative solutions to these issues by enhancing transparency, security, and operational efficiency. However, adoption among Kenyan DT-SACCOs remains critically low due to organizational barriers that have yet to be fully explored. This study investigated the organizational factors influencing blockchain adoption among DT-SACCOs in Kenya. Specifically, it examined the role of corporate governance (e.g., board size and ICT committees), financial health (e.g., profitability, liquidity, and asset quality), and firm characteristics (e.g., size and age) in shaping adoption decisions. The research was anchored on four theories: Institutional Theory, Organizational Readiness for Change Theory, the Technology Acceptance Model (TAM), and the Diffusion of Innovations Theory. A positivist philosophy and a quantitative cross-sectional design were adopted. The target population was approximately 352 managerial-level staff drawn from all 176 licensed DT-SACCOs in Kenya, with a sample size of 187 determined using Yamane's formula. Primary data were collected through structured questionnaires. Secondary financial data from SASRA (2023) was also used to complement the primary data. Data analysis involved descriptive statistics and binary logistic regression models to assess the likelihood of blockchain adoption. The findings revealed that SACCOs with larger boards and dedicated ICT committees were likelier to adopt blockchain technology due to improved decision-making and strategic alignment. Financially stable SACCOs with high profitability and liquidity demonstrated greater readiness for blockchain investment. Firm size positively influenced adoption due to access to resources and economies of scale, while older SACCOs resisted change due to rigid operational structures. The study highlighted the critical role of internal organizational factors in blockchain adoption among Kenyan DT-SACCOs. Strengthening corporate governance frameworks, improving financial health and fostering innovation-friendly cultures are essential for accelerating blockchain integration. The findings have significant implications for policymakers, regulators and SACCO managers seeking to enhance operational efficiency, reduce fraud and ensure long-term competitiveness in the evolving financial landscape. The study was limited to responses from DT-SACCOs, which may not fully capture the diversity of views within each organization. Additionally, the cross-sectional nature of the data limits the ability to draw causal inferences.
Full - text thesis